CuCr Bimetallic Catalyst for Selective Electrooxidation of Ammonia at Room Temperature. Issue 7 (16th March 2023) - Cleetus, Annie; Teller, Hanan; Schechter, Alex
Abstract: In an effort to attain a low‐cost, energy‐efficient, and non‐noble electro‐catalyst that selectively oxidises ammonia to nitrogen at room temperatures, bimetallic carbon‐supported Cux Cry (x, y=1–9) catalysts were prepared and found to be more active than elemental Cu and Cr towards ammonia oxidation (AOR). Cyclic voltammetry (CV) measurements revealed an increase in activity with Cu content. Peak current density of 90 % Cu catalyst in 0.1 M KOH+0.1 M NH4 OH was found to be 22 mA/mg (scan rate=20 mV/s) compared with 14.8 mA/mg for commercial Pt catalyst under the same conditions. Mass spectrometry measurements have identified higher selectivity of this catalyst towards N2 than on Cu alone. Pre‐oxidation of catalyst in 0.1 M KOH (1.1 V vs RHE) was found to improve the activity and stability towards AOR over time. The potential of Cux Cry (x, y=1–9) based catalysts for AOR in fuel cells is corroborated. Abstract : Non‐noble bimetallic CuCr catalysts were analyzed as potential catalysts for ammonia oxidation. A catalyst with 90 % of Cu with a current density of 22 mA/mg was found to be even more active than Pt (14 mA/mg) under the same conditions. The selectivity towards nitrogen and stability of the catalysts were also explored.